Validity of a questionnaire measuring the world health organization concept of health system responsiveness with respect to perinatal services in the dutch obstetric care system - van der Kooy, Jacoba (BMC Health Serv Res, 2014)
BACKGROUND: The concept of responsiveness, introduced by the World Health Organization (WHO), addresses non-clinical aspects of health service quality that are relevant regardless of provider, country, health system or health condition. Responsiveness refers to “aspects related to the way individuals are treated and the environment in which they are treated” during health system interactions. This paper assesses the psychometric properties of a newly developed responsiveness questionnaire dedicated to evaluating maternal experiences of perinatal care services, called the Responsiveness in Perinatal and Obstetric Health Care Questionnaire (ReproQ), using the eight-domain WHO concept. METHODS: The ReproQ was developed between October 2009 and February 2010 by adapting the WHO Responsiveness Questionnaire items to the perinatal care context. The psychometric properties of feasibility, construct validity, and discriminative validity were empirically assessed in a sample of Dutch women two weeks post partum. RESULTS: A total of 171 women consented to participation. Feasibility: the interviews lasted between 20 and 40 minutes and the overall missing rate was 8%. Construct validity: mean Cronbach’s alphas for the antenatal, birth and postpartum phase were: 0.73 (range 0.57-0.82), 0.84 (range 0.66-0.92), and 0.87 (range 0.62-0.95) respectively. The item-own scale correlations within all phases were considerably higher than most of the item-other scale correlations. Within the antenatal care, birth care and post partum phases, the eight factors explained 69%, 69%, and 76% of variance respectively. Discriminative validity: overall responsiveness mean sum scores were higher for women whose children were not admitted. This confirmed the hypothesis that dissatisfaction with health outcomes is transferred to their judgement on responsiveness of the perinatal services. CONCLUSIONS: The ReproQ interview-based questionnaire demonstrated satisfactory psychometric properties to describe the quality of perinatal care in the Netherlands, with the potential to discriminate between different levels of quality of care. In view of the relatively small sample, further testing and research is recommended. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-014-0622-1) contains supplementary material, which is available to authorized users.